Порівняльний аналіз RFID-систем та аналогічних систем контролю доступу - Вініцький, М. А. (ХНУРЕ, 2025)
This study provides an in-depth comparison between RFID-based and bio metric access control systems, focusing on security, authentication speed, cost efficiency, and user experience. RFID offers rapid authentication and flexibility, while biometric technologies provide enhanced security by eliminating the risks of credential duplication and unauthorized access. The paper explores key vulnerabilities of both approaches, assesses their suitability for different security levels, and suggests an optimal hybrid model for secure access management.
Keywords: RFID-система; система контролю доступу